Analisis Model Pembelajaran SAVI (Somatis, Auditori, Visual, dan Intelektual) dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Fikih - Muhammad Kholil; Maimun Sholeh (FONDATIA, 2021)
This study aims to analyze the SAVI learning model (Somatic, Auditory, Visual, and Intellectual) to improve student learning outcomes in fiqh subjects. This research is classified as classroom action research (CAR). Data collection was carried out using tests. The design of the classroom action research model is applied in several cycles. Each cycle includes four stages, namely: planning actions, implementing actions, observation / evaluation and reflection. The subjects of this study were fourth grade students of MI Darus Salam Prasi, Gading District, Probolinggo Regency, which collected 20 students. The results showed that the SAVI learning model had a positive impact on student learning outcomes. This can be seen in student learning outcomes which have increased in cycle I. The level of completeness of 20 students reaches 65%, with an average score of 72. In cycle II, the level of completeness reaches 90% of 20 students. the average score is 81 points. The results of the study can be said that the SAVI learning model has a significant effect on improving students' fiqh learning outcomes.